THE EFFECTIVENESS OF PROBLEM BASED LEARNING (PBL) APPROACH VIEWED FROM THE STUDENTS’ MATHEMATICAL CREATIVE THINKING ABILITY - Lisda Fitriana Masitoh (STKIP Singkawang, 2019)
Generally, mathematical competence equips students with logical thinking ability. On the other hand, the mathematical competence is expected to equip students with creative thinking ability. Creative thinking ability is used when a person faces a problem or challenge. Nowadays, there has been a lot of developing approaches that can be used to create ideal learning condition to achieve the learning goals, including improving the mathematical creative thinking ability. One of approaches that can be used is Problem Based Learning (PBL). The purpose of this research was to describe the effectiveness of PBL approach in terms of mathematical creative thinking ability. This was a quasi-experimental reseach. A control class used the conventional approach. The results showed that Problem Based Learning (PBL) was an effective appoach viewed from the mathematical creative thinking ability. Meanwhile, the control class was not effective.